Modified failure mode and effect analysis to mitigate sustainable related risk in the palm oil supply chain - Anugerah, Adhe Rizky; Ahmad, Siti Azfanizam; Samin, Razali; Samdin, Zaiton; Kamaruddin, Norfaryanti (Taylor & Francis, 2021)
The increasing complexity and the special characteristics of palm oil supply chain lead the companies to be exposed to more risks. Failure in managing supply chain risk can generate huge losses for organisations. In order to maintain its existence and be more sustainable, palm oil industries should not only focus on the economic aspect but also the environmental and social aspects. This research aims to establish risk management to decrease the consequences of possible risks in the palm oil plantation supply chain. Failure Mode and Effect Analysis (FMEA) combined with the Analytical Hierarchy Process (AHP) were used to perform risk management processes. The data were collected through a survey at the management level of a case study company. The results showed that the unsafe and dangerous working environment, natural disasters, and unreliable transportation systems are the most dangerous risk. The proposed modified approach to risk management has been able to improve accuracy in prioritising the sustainable related risk in the palm oil supply chain.